answersLogoWhite

0


Best Answer

b2(b + 6)

User Avatar

Wiki User

โˆ™ 2012-05-03 03:24:35
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is the factor of b3 plus 6b2?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

How do you factor 6a2 plus 5ab - 6b2?

6a2 + 5ab - 6b2 = (3a - 2b)(2a + 3b)


Which is a factor of 6a2 plus 5ab - 6b2?

6a2 + 5ab - 6b2 = 6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)*(3a - 2b)


How do you factor 6ab - 6ac plus 6b2 - 6bc?

6(a + b)(b - c)


Is b plus 4 a factor of b3 plus 3b2 minus b plus 12?

Yes.


What is the factor polynomial 6b2-15b3?

-3b2(5b - 2)


Which is a factor of 6a2 5ab - 6b2?

(3a - 2b)(2a + 3b)


How do you factor out 6b2-15b-6?

3(2b2 - 5b - 2)


How do you factor 6b2-7b-20?

(-3b - 4)(-2b + 5)


A3 plus b3 equals?

A3+b3


Which is a factor of 6a2 plus 5ab 6b2?

Considering the minus sign between 5ab and 6b2 then we have the polynomial as 6a2 + 5ab - 6b2. The polynomial is a quadratic polynomial.Steps to factorize a quadratic polynomial:1 - Multiply first term by third term. 6a2 x (-6b2) = -36a2b22 - If possible break the second term into two terms such that they multiple to -36a2b2. If not then it is factorized by Sridharacharya's formula.5ab can be broken as 9ab + (-4ab).These two terms multiply to give -36a2b2.So we can write 6a2 + 5ab - 6b2 = 6a2 + 9ab + (-4ab) - 6b2.6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)(3a - 2b).So the factors are (2a + 3b) and (3a - 2b).


What is the greatest common factor of c2 and b3?

The GCF is 1.


Formula for a3 plus b3 plus c3?

kutta


Factor b3 - 5b2 plus 12?

b3 - 5b2 + 12 = (b - 2)(b2 - 3b - 6)Check:(b - 2)(b2 - 3b - 6)= b(b2 - 3b - 6) - 2(b2 - 3b - 6)= b3 - 3b2 - 6b - 2b2 + 6b + 12= b3 - 5b2 + 12


In Excel what does plus mean?

The plus is the symbol used for addition in Excel. To add the contents of cell A3 and B3 you would do the following: =A3+B3


What is the formula of a3 plus b3?

(a+b)3=a3+b3+3ab(a+b) a3+b3=(a+b)3-3ab(a+b) a3+b3=(a+b)(a2-ab+b2)


How do you factor for cubes?

a3 + b3 = (a + b)(a2 - ab + b2) a3 - b3 = (a - b)(a2 + ab + b2)


How do you factor the trinomial 6b2-13bs-63s2?

6b^2-13bs-63s^2 is factorised to (2b-9s)(3b+7s)


What is the answer to 5 plus b3?

5 + b3 cannot be solved since it is not an equation. It is simply a combination of 2 terms.


What sign is used for addition in Excel?

The plus sign. + To add values in the cells A3 and B3 you would do the following: =A3+B3


How do you factor difference of cubes?

a3 - b3 = (a - b)(a2 + ab + b2)


How do you do you factor the sum and difference of two cubes?

a3 + b3 = (a + b)(a2 - ab + b2) a3 - b3 = (a - b)(a2 + ab + b2)


How do you factor the sum and difference of two cubes?

a3 + b3 = (a + b)(a2 - ab + b2) a3 - b3 = (a - b)(a2 + ab + b2)


WHAT IS a to the power 3 plus b to the power 3?

a3+b3


What are possible answers to a3 equals b3 plus c3?

There are no whole solutions


How do you factor a raised to 6 - b raised to 6?

0